Cardiac contractility modulation in heart failure patients: Randomized comparison of signal delivery through one vs. two ventricular leads. Issue 1 (January 2017) - Röger, Susanne; Said, Samir; Kloppe, Axel; Lawo, Thomas; Emig, Ulf; Rousso, Benny; Gutterman, David; Borggrefe, Martin; Kuschyk, Jürgen
Abstract: Background: Cardiac contractility modulation (CCM) is an electrical stimulation treatment for symptomatic heart failure (HF) patients. The procedure involves implantation of two ventricular leads for delivery of CCM impulses. The purpose of this study is to compare the efficacy and safety of CCM when the signal is delivered through one vs. two ventricular leads. Methods: This prospective blinded randomized trial enrolled 48 patients. Eligible subjects had symptoms despite optimal HF medications, left ventricular ejection fraction <40% and peakVO2  ≥ 9 ml O2 /kg/min. All patients received a CCM system with two ventricular leads, and were randomized to CCM active through both or just one ventricular lead; 25 patients were randomized to receive signal delivery through two leads (Group A) and 23 patients to signal delivery through one lead (Group B). The study compared the mean changes from baseline to 6 months follow-up in peakVO2, New York Heart Association (NYHA) classification, and quality of life (by MLWHFQ). Results: Following 6 months, similar and significant ( p  < 0.05) improvements from baseline in NYHA (−0.7 ± 0.5 vs. −0.9 ± 0.7) and MLWHFQ (−14 ± 20 vs. −16 ± 22) were observed in Group A and in Group B. PeakVO2 showed improvement trends in both groups (0.34 ± 1.52 vs. 0.10 ± 2.21 ml/kg/min; p  = ns). No patient died. Serious adverse event rates (20 events in 10 subjects) were not different between groups. No statistically significant difference was found in any of the study endpoints. Conclusions: The efficacy and safety of CCM in this study were similar when the signal was delivered through either one or two ventricular leads. These results support the potential use of a single ventricular lead for delivery of CCM.